REGIONAL STOCK MARKETS AND GLOBAL ECONOMIC CYCLES - Vasylchenko, S.M.; Malyshivski, T.V. (The actual problems of regional economy development, 2019)
The article examines the relationship between financialization of economies of the leading countries of the world and the nature of the modern global economic cycle. Since 1999, the phenomenon of “financialization of the economy” has been observed in the global economy. Due to financialisation of the modern economy financial markets became the generators of the business cycle. Exactly the instability of financial markets provoke a business cycle. The authors of the article suggest that due to certain laws of functioning of the stock market it is possible to predict the period of the global economic cycle which will prevent its devastating impact on the world economy. What determines the duration of the current economic cycle (the period of the economic cycle) in the modern global economy, is it possible to determine in time the probability of the onset of another recession? These issues remain poorly researched and that is why are very actual taking into account the destructive nature and the planetary scale of the social and economic consequences of the modern global cycle. According to our estimates the period of the global economic cycle is 7-8 years. The analysis of the dynamics of economic growth and stock markets of the leading countries of the world gives us a reason to expect that the next financial crisis can happen already in 2022-2023.